BIOACARICIDE ACTIVITY OF SAPPAN WOOD (Caesalpinia Sappan L.) INFUSION AGAINST TICKS BOOPHILUS MICROPLUS IN CATTLE - Sukmawati, Sukmawati; Fahrodi, Deka Uli; Marsudi, Marsudi; Said, Nur Saidah; Khaliq, Taufik Dunialam (JURNAL NUKLEUS PETERNAKAN, 2024)
This research aims to exploit the potential of sappan wood (Caesalpinia sappan L.) as a bioacaricide on Boophilus microplus ticks. This research used a completely randomized design method with ticks as the research object. There were five treatments in this study, two of which were in the positive control group (Kututox) and negative control (Aquades), and three treatments in the group were given sappan wood infusion with concentrations of 25%, 50%, and 75%. Each treatment consisted of 5 replications, each replication using five ticks. The sappan wood infusion bioacaricide test was carried out in vitro, and tick death was observed for 5 hours with observation time every hour after spraying. The data obtained were analyzed using one-way variance, followed by the LSD test. Then, a probit analysis of LC50 and LC90 was performed to determine the concentration of sappan wood infusion that can kill ticks, and LT50 and LT90 were used to determine the time of death of B. microplus ticks. The research results showed that sappan wood infusion with a concentration of 75% effectively killed 50% of Boophilus microplus ticks at 0.67 hours and killed 90% of Boophilus microplus ticks at 1.17 hours. Sappan wood infusion can be an alternative bioacaricide to kill Boophilus microplus ticks